Analisis Perbedaan Penyusunan Laporan Keuangan Konsolidasi pada Perusahaan di Indonesia dengan Konvergensi IFRS dan PSAK 22 - Cinta Nikita Aulia; Devi Mayasari; Ayuni Affina Hernawan; Caroline Sima Br Ginting; Bana Ahmad Gautama (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The purpose of this study is to determine how IFRS 22 and IFRS 3 differ from each other with respect to business combinations as they relate to the compilation of consolidated financial statements for Indonesian companies. Because this strategy gives researchers an idea of how the topic of debate has evolved, a qualitative method that uses a review literature approach is the type of method used. Secondary data that has been examined to generate a description of the research topic is the source of the data used. The study shows that IFRS 22 and IFRS 3 differ in several areas, including the presentation of long-term liabilities that must be refinanced, minority interest rate requirements, disclosures in financial position statements, and financial statement components. Consolidated financial statements based on IFRS number 3 and PSAK number 22 must be prepared for the combination of companies. Guidelines for reporting consolidated financial statements for companies with subsidiaries are listed in PSAK number 22. Guidance on the accounting treatment of corporate purchases is provided by IFRS 3. The components of the financial statements, the disclosures in the statement of financial position, the term minority interest, extraordinary headings, and the reporting of long-term liabilities to be refinanced are where PSAK 22 and IFRS 3 differ. It is important for all businesses to have a comprehensive understanding of the relevant guidelines and regulations to guarantee the accuracy and compliance of consolidated financial statements with such accounting standards. It is important to speak with a qualified financial advisor or professional accountant if further details or a more thorough explanation are needed.